(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The subject of the organizational Ambidexterity of the vital Topics through which it seeks organizations to provide mentalities renewable for their members and maintain its survival and continuity according to different organizational methods of access for strategic success. The research aims to demonstrate the impact of organizational Ambidexterity in achieving strategic success in the National bank of Iraq, and the questionnaire was prepared as a tool for collecting data and information through sample survey of (16) managers and heads of departments , The results were analyzed by using the statistical program (SPSS) in calculating mean, standard deviation, percent and test (f), coefficient determination. The results revealed a high level of leadership in the bank to the dimensions of the organizational Ambidexterity that led the bank towards Strategic success , In light of the findings the researchers presented a set of recommendations.